Educação - Corporeidade - Lazer: saber da experiência cultural em prelúdio - França, Tereza Luiza de (2003)
In the passage of life, the labyrinth of songs and corners are propitious ways for a better comprehension, perception and incorporation of learnings that emerge from our subjectiveness in a magic caught by senses. Eyesight, taste, hearing, touch and smell in communication with the world, put us in front of cultural diversities. The ludicity accumulated by experiences promote the flow of hilarious and concrete discoveries that express themselves in work and leisure demonstrations. Such reflections emerge indicators to the problematic construction centralized in the incorporation of cultural experience knowledge to the formation process and professional interventions in this rule and area. From this significant problematic, aiming to deepen studies, we favored leisure as field of investigative production in full expansion. This, for sure, was an exercise of qualification that guided us through meander of education and made us dip into studies about the corporeity. A research in which the scenery was painted and constructed with the complicity of the culture lived with shine, colors, rhythm and drummings of one of the most present cultural cycles: carnival. Recognized as a stimulant for beauty, participation, socialization, and helped us to enter in the essence of gestures and expressions of corporeity, to think, elaborate and socialize a critic-scientific knowledge which, appropriating from the rhythm of colors, of sounds, of tonalities, of senses and of meanings impregnated in the web of life. All these things seduced the researcher, making imagination flow amid ludic-creative dialogues with the imaginary of researchers creation and production in the rule and area of leisure, education and corporeity. Option that made us outline as objective to investigate and interpret how leisure teachers-researchers, from their studies, researches and interventions, locate and incorporate the knowledge from cultural experience to the formation process and intervention of professionals in this rule and in this area, emphasizing the contributions from this knowledge to fence and qualify this praxis. So, as living each cultural scenery, each epistemological contribution was feeding the production with images of the different versions of the Brazilian breedings, creating and raising expectations and new discoveries and newcomers. With the seriousness of a scientific study, we lived an xxiii academic experience with complex intensity, rigor and coherence, eliminating, step by step, the risks and limitations always present in a work of this magnitude. However, we weren t, even for one moment, alone. Our epistemic regard always maintained mediated by the principles of a methodological approach - the Etnomethodology, that while central guide provided us clues to unveil the lived world by our people-playful , in a universe of 15 members, that allowed themselves to comprehend, comment, analyze. This way, grasping the object in interactions arised and provoked by narrative interview, it was systematically dialected by (re) interpretation of images and formulations of people-playful, enriched by their beliefs, myths, conceptions and rituals inherent to knowledge from cultural experience, which each one attuned with Brazilian and international history, in a mixture of senses echoed from songs and tales. Inspired in drummings and percussions, clothing and choreographies of gestures and expressions, in mixtures produced in unit interactions in the multiplicity shown as necessary requests to the totality of life, with ludicity the rescue of the past, the conquest of present and the construction of future was the axle guide. This rich process of scientific creation made us realize that is possible qualify and empower the praxis in the rule and area of leisure incorporating the knowledge from cultural experience. What also becomes possible is the recuperation of objective revolutionaries and changing conditions of praxis itself with the view of strengthening and triggerment of vital elements in the rule and area of leisure. We also reaffirm that from this praxis emerge elements necessary to human formation in plenitude, by the appropriation of knowledge that guide the facing of challenges of a complex and plural world that valorize education, corporeity and leisure